The influence of political socialization among educated youth at Universiti Putra Malaysia - Ismail, Mohd Mahadee; Hassan, Nor Azlili; Md Nor, Mohd Sabri; Mohd Zain, Mohd Izani; Ku Samsu, Ku Hasnita (Human Resource Management Academic Research Society, 2021)
This article discusses the influence of political socialization among educated youths in Malaysia, with special focus given to Universiti Putra Malaysia (UPM) students. The political learning process of youth groups is essential to be refined from time to time, especially in political socialization everyday defined until they reach a stage of maturity in their life. Many factors and agents are involved in the process of political socialization of an individual. Therefore, this article focuses on the factors and agents of political socialization that influence the learning process of political affairs among UPM students. This study used a quantitative approach with survey techniques using a self-administered questionnaire involving 431 educated Malay and Chinese youth for comparison in studying the influence of political socialization. This study showed that there are different variations on the influence of political socialization among Malay and Chinese youth. Each agent has its role in influencing the political socialization of the youth groups being studied. Ironically, the learning process about the political affairs of these educated youths is significantly influenced by educational and government factors and the family and peer group factors that have a strong influence, particularly in their literacy formation and political awareness.